REGULATION OF LOBBYING IN LITHUANIA AND THE STANDARDS OF OECD - Ambrasaitė, Monika (Teisė, 2017)
On 23 of June 2016 the Draft of Republic of Lithuania Law changing Law on Lobbying Activities no. VIII-1749 (new edition) no. XIIP-2731(2) was introduced. The draft is an attempt to reform regulation of lobbying of Lithuania, which is recognized as ineffective. After 4th of June 2015 when Lithuania was officially invited to begin the process of accession to the Organisation for Economic Co-operation and Development it became necessary to harmonize the regulation of lobbying with the Recommendation of the Council of the Organisation for Economic Co-operation and Development on Principles for Transparency and Integrity in Lobbying no. C(2010)16. In this paper the (non)conformity of the draft to the guidelines of mentioned recommendation is analysed and recommendations for improvement of the regulation of lobbying are presented.